3D printing of hollow lattice structures of ZrO2(3Y)/Al2O3 ceramics by vat photopolymerization: Process optimization, microstructure evolution and mechanical properties. (November 2022) - Zhang, Lizheng; Liu, Hao; Yao, Haihua; Zeng, Yong; Chen, Jimin
Abstract: 3D printing technology was introduced into the manufacturing of ceramic components. To obtain a new lightweight multifunctional structure with novel structure and excellent performance, and promote the deep combination of additive manufacturing and optimization design, ZrO2 (3Y)/Al2 O3 hollow lattice structure ceramics with two kinds of high precision and different porosity were prepared by vat photopolymerization in this paper, and the process optimization, microstructure evolution, and performance were studied. The hollow lattice structure with good molding accuracy and porosity of 35 %–55 % was prepared by component design, optimization of slurry, degreasing, and sintering process, which effectively avoided the ceramic cracking and collapse caused by resin volatilization. When the Al2 O3 content was 6 wt%, dense ZrO2 (3Y)/Al2 O3 ceramics with grain refinement, excellent microhardness, and fracture toughness were obtained. The relationship between lattice structure and compressive strength was analyzed by simulation and compressive test. The results show that the compressive strength of the two hollow lattice structures decreases with the increase of porosity. The maximum compressive strength of 35 %-face-centered cubic (FCC) hollow lattice structure is 326 MPa, which is significantly higher than that of body-centered cubic (BCC) structure (240 MPa) with the same porosity. The hollow lattice ceramic structure with good comprehensive performance and lightweight will lay a foundation for the application of industrial heat insulation, high temperature catalysis, and purification carrier in the future. Graphical abstract: Unlabelled Image